PRINCIPALES PROBLEMAS METODOLÓGICOS EN LA ENSEÑANZA DEL SUBSISTEMA FONÉTICO-FONOLÓGICO ESPAÑOL EN EL ÁMBITO DE LOS ESTUDIOS UNIVERSITARIOS POLACOS - Szałek, Jerzy (Neofilolog, 2019)
The problems concerning teaching methodology in the domain of phonetics and phonology of Spanish have not as yet been properly addressed within the considerably young Polish studies of the Spanish language. The author of the present article, based on his own research and teaching experience, suggests a number of solutions and practical remarks related to teaching methodology of contemporary Spanish phonetics and phonology within Spanish language and literature studies in Poland. The so-called ”comprehensive approach” has been verified for compliance with the most recent achievements of modern Spanish phonetic and phonological studies.